2008
DOI: 10.1121/1.2933803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Japanese expressive speech perception by Japanese and Taiwanese listeners

Abstract: Language is an important tool in speech communication. Even without the understanding of one language, we can still judge the expressive content of a voice, such as happiness or sadness. However, sometimes misunderstanding of emotional communication occurs. It is not clear what the common/different features are that help or hinder people with different culture/native-languages background in making judgments about the expressivity of speech. In order to explore this question, we focus on Japanese and Taiwanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The majority of studies also used a forced-choice method wherein participants were asked to choose their response from a list of predefined response alternatives. However, a couple of studies that used rating scales or free responses were included because they also provided data on the proportion of accurate responses (Abelin & Allwood, 2000; Gendron, Roberson, van der Vyver, & Barrett, 2014; Huang, Erickson, & Akagi, 2008). The accuracy criterion excluded studies that investigated emotion recognition using dimensional ratings (e.g., activation, valence, emotion intensity, appraisal dimensions)—which do not provide measures of accuracy (e.g., Koeda et al, 2013; Nordström, Laukka, Thingujam, Schubert, & Elfenbein, 2017; Pfitzinger, Amir, Mixdorff, & Bösel, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of studies also used a forced-choice method wherein participants were asked to choose their response from a list of predefined response alternatives. However, a couple of studies that used rating scales or free responses were included because they also provided data on the proportion of accurate responses (Abelin & Allwood, 2000; Gendron, Roberson, van der Vyver, & Barrett, 2014; Huang, Erickson, & Akagi, 2008). The accuracy criterion excluded studies that investigated emotion recognition using dimensional ratings (e.g., activation, valence, emotion intensity, appraisal dimensions)—which do not provide measures of accuracy (e.g., Koeda et al, 2013; Nordström, Laukka, Thingujam, Schubert, & Elfenbein, 2017; Pfitzinger, Amir, Mixdorff, & Bösel, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Low arousal and negative valence speech easily make an impression on listeners with dark and heavy feelings, but high arousal and positive valence speech is oftentimes uttered in a bright and well-modulated way. The set of semantic primitives derived from [4] that we examined and used in the three-layer model for describing emotional speech was: bright, dark, high, low, strong, weak, calm, unstable, well-modulated, monotonous, heavy, clear, noisy, quiet, sharp, fast, and slow. To construct the three-layer model, the three emotional corpora were first evaluated in terms of each semantic primitive through human listening tests.…”
Section: Primitives-based Emotion Evaluationmentioning
confidence: 99%
“…The purpose is to create a natural human-machine interaction in a real-world-context [1]. These days, psychology has proven that the human ability to perceive emotions is cross-lingual with no utterance required in his/her native or foreign language [2][3][4] . Despite great progress made in SER, natural human-behavior interaction is still an obstacle, on the grounds that there is a strong dependence on the language being spoken, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…People can still judge the expressive content of a voice for one language, such as emotional states, even without the understanding of that language [6]. Several studies have indeed shown evidence for certain universal attributes for speech [7], not only among individuals of the same culture, but also across cultures.…”
Section: Introductionmentioning
confidence: 97%